Developing Journey in Integria: A web-based educational application for conceptual learning of integer operations - Rino Sinus Pandanu (Eduvista: Journal of Education and Innovation, 2026)
Integer operation learning media are still predominantly based on static representations that provide limited support for students’ conceptual understanding, while web-based instructional media integrating dynamic visualization and interactivity remain relatively limited. This study aims to develop Journey in Integria, a web-based educational application for learning integer operations using HTML, CSS, and JavaScript. The research employed the Luther-Sutopo multimedia development model consisting of concept, design, material collecting, assembly, testing, and distribution, while functional evaluation was conducted through Black Box Testing. The results demonstrate that the application successfully integrates dynamic number-line visualization, character animation, step-by-step solution logs, and interactive input features into a browser-based learning environment accessible across multiple devices without additional installation. All application functions operated according to the predefined specifications, and the application was successfully deployed through GitHub Pages for public access. This study contributes a web-based instructional medium that has the potential to support conceptual understanding of integer operations through integrated visualization and interactive learning experiences. Abstrak Media pembelajaran operasi bilangan bulat umumnya masih didominasi oleh representasi statis sehingga kurang mampu memfasilitasi pemahaman konseptual, sementara pengembangan media berbasis web yang mengintegrasikan visualisasi dinamis dan interaktivitas masih relatif terbatas. Penelitian ini bertujuan mengembangkan aplikasi Journey in Integria sebagai media pembelajaran operasi bilangan bulat berbasis HTML, CSS, dan JavaScript. Penelitian menggunakan metode pengembangan multimedia Luther-Sutopo yang meliputi tahap concept, design, material collecting, assembly, testing, dan distribution, sedangkan pengujian dilakukan menggunakan Black Box Testing. Hasil penelitian menunjukkan bahwa aplikasi berhasil mengintegrasikan visualisasi garis bilangan, animasi karakter, log penyelesaian bertahap, serta panel input interaktif dalam satu platform berbasis web yang dapat diakses melalui berbagai perangkat tanpa instalasi tambahan. Seluruh fitur berfungsi sesuai spesifikasi yang dirancang dan aplikasi dipublikasikan melalui GitHub Pages sehingga siap dimanfaatkan sebagai media pembelajaran. Penelitian ini berkontribusi dengan menghadirkan media pembelajaran berbasis web yang berpotensi mendukung pemahaman konseptual operasi bilangan bulat melalui visualisasi dan interaktivitas yang terintegrasi.